IT-sicherheit : Konzepte - Verfahren - protokolle - Eckert, Claudia (De Gruyter Oldenbourg, 2014)
<!Doctype html public ""-//w3c//dtd html 4.0 transitional//en""> This book systematically describes important aspects when planning secure IT systems, as well as the different approaches that may be used. It presents procedures and protocols in detail and explains them with case examples. This book is a must-read for anyone involved in IT security.